Looking for Cosy in All the Wrong Places. Cosiness and Tamed Sublime of "No Man’s Sky" - Tomasz Gnat (Replay)
In this article, I argue that some games may elicit cosy sentiments even if they are centred on a premise not usually associated with cosiness – for example the infinity of the universe. They do so not by a fluke, and cosy spaces in these games do not only appear as designated spaces apart. Evoking a cosy feeling is done by specific game mechanics or design choices, “taming” the sublime premise of the game discussed. The architecture and mechanics of this unexpected cosiness may offer a new look at the fringe cases of cosy aesthetics, perhaps broadening the understanding of this phenomenon.